Analisis Kesulitan yang Dihadapi Peserta Didik Pada Mata Pelajaran Ekonomi SMA 2 Rejang Lebong - Herwan MDK; Azlika Aryani (Jurnal Multidisiplin Dehasen (MUDE), 2022)
The purpose of the study was to find out the difficulties faced by students in economic subjects at SMAN 2 Rejang Lebong and to find out the efforts made by teachers to overcome students' learning difficulties in economic subjects in SMAN 2 Rejang Lebong class. The type of research is the type of research used in this research is descriptive qualitative research. Data collection techniques are 1) observation, 2) interviews, 3) documentation. The data analysis techniques are 1) data collection, 2) data reduction, 3) data display, 4) conclusion drawing. The results and discussion in the study are 1) Students who have learning difficulties show an unnatural attitude (Social). Low student academic achievement (Academic). Difficulty making new understandings (Metacognition). Students are slow in processing something (Processing speed). Students find it difficult to interpret what is felt, heard, and seen (Perception). Students lack attention and focus in learning (Attention). Too many activities that are less useful that students do so it is difficult to remember the subject matter (Memory)..